Bajki Adama Naruszewicza wobec innych realizacji gatunku w Oświeceniu - Petlak, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
Frugal literary legacy of Adam Naruszewicz (be was an author of fairy-tales) has never been a subject of circumstantial research. It has never aroused any acknowledgement among literary historians. This very fact encouraged me to deeper learning of fairy-tale craft of this outstanding poet. I also came to the conclusion that particular qualities of fairy-tales by Naruszewicz would be more meaningful if I made a comparison of his creative work features with those of other representatives of this literary genre of the second half of the 18th century, i.e. Stanislaw Trembecki, Ignacy Krasicki and Julian Ursyn Niemcewicz. Although Naruszewicz takes a substantial place in the Age of Enlightenment it seems that certain features of his poetry present in the fairy-tales can be found in works of certain representatives of this genre; his fairy-tales are an interesting stage of story-telling branch of this literary form.